Nyheder og/eller falske nyheder? Nyhedsformidling i Calderón og Coellos Underet i Tyskland - Kluge, Sofie (K&K - Kultur og Klasse, 2020)
Taking off from El prodigio de Alemania [The Wonder in Germany, 1634], a recently discovered collaborative play by Calderón and Coello about general Albrecht von Wallenstein, this article discusses the conception of factuality informing Golden Age dramatic representations of contemporaneous history. Vis-à-vis the recurrent critical disparagement of this type of drama as artistically inferior propaganda, I will demonstrate the dramatists’ delicate handling of the breaking news about Wallenstein’s death and their use of advanced aesthetic and performative devices to stimulate audience thinking about Wallenstein’s destiny: Why did he become a traitor? Highlighting the subtle doublespeak informing especially the epilogue and the protagonist’s great monologue, I will argue that the play is at once loyal and critical toward Habsburg policy: it follows the official explanation of the general’s murder — that he was planning high treason — yet at the same time demonstrates an essentially interrogatory conception of factuality that invites reflection on what is historical “truth”.